MODEL PENGUKURAN KINERJA INTELLECTUAL CAPITAL DENGAN IB-VAIC DI PERBANKAN SYARIAH - Ihyaul Ulum (State Institute of Islamic Studies (IAIN) Salatiga, 2013)
The aim of this study is to develop a measurement of intellectual capital performance of Indonesian syariah banking by modifying the Pulic’s model that popular with the name of VAIC (value added intellectual coefficient). This study was done by documentation and focus group discussion with some financial accounting experts and public accountants. The result show that the main formula to measure IC performance of syariah banking is not too different with Pulic model, it was: iB-VAIC™ = iB-VACA + IB-VAHU + iB-STVA. The different one is the accounts to develop VA. VA in Pulic model was constructed by total revenue, while in iB-VAIC, VA was constructed from syariah activities.